TRANSIENT MODEL OF A STATIC EVAPORATOR FOR AN AIR-WATER HEAT PUMP - Oliveira, R. N.; Reis, R. V. M.; Koury, R. N. N.; Machado, L. (Revista de Engenharia Térmica, 2011)
The increasing demand of electric energy in Brazil, allied to the great consumption in rush hour, has stimulated the study of water heating systems that substitute the electric shower. One of these equipments, the solar collector, is the most viable, with the best cost-benefits relation, because Brazil is a tropical country. A heat pump can be used as a support to solar collectors in places where the climatic conditions and/or the lack of available area of solar collection limit the use of the system. One way to improve this heat pump would be the substitution of its conventional evaporator for a static evaporator. This evaporator is constituted of a metallic plate with conformed canals, inside of which the coil is fixed through which the refrigerator cooling of the heat pump flows. The objective of this paper is the development of a mathematical model in transient regimen to simulate the static evaporator operation of an air-water heat pump. Some simulations had been carried through, that had allowed testing geometric parameters of the system, materials for the pipes and plates and different weather conditions. These computational tests had indicated that the model represents a good tool to project static evaporators.